Floristic and phytosociological analysis of palm swamps in the central part of the Brazilian savanna - Isa Lucia de Morais Resende; Lázaro José Chaves; José Ângelo Rizzo (Acta Botânica Brasílica, 2013)
We analyzed the floristics and phytosociology of three palm swamps in the municipality of Bela Vista de Goiás, located in the state of Goiás, Brazil, in the central part of the Brazilian savanna (Cerrado). The floristic surveys were conducted monthly from May 2008 to April 2009, and 310 species were recorded (seven bryophytes, 15 ferns and 288 angiosperms). Bryophytes belonged to five genera and five families; ferns belonged to nine genera and nine families; and angiosperms belonged to 134 genera and 45 families. The angiosperm families with the highest species richness were Poaceae, Cyperaceae, Asteraceae, Eriocaulaceae, Xyridaceae, Lentibulariaceae, Melastomataceae, Rubiaceae and Fabaceae. The palm swamps were divided into three zones of increasing humidity: edge, middle and core. The number of species was higher in the middle than at the edge and the core. The families with the highest cover values were Cyperaceae, Melastomataceae, Arecaceae and Poaceae. Although the palm swamps had been disturbed to varying degrees, those disturbances did not affect the flora in the middle or the core. Floristic similarity was high between these two zones within a given palm swamp and low between the edges of different palm swamps.